Synergistic Chemotherapy Drug Response Is a Genetic Trait in Lymphoblastoid Cell Lines - Roell, Kyle R.; Havener, Tammy M.; Reif, David M.; Jack, John; McLeod, Howard L.; Wiltshire, Tim; Motsinger-Reif, Alison A. (Frontiers in Genetics, 2019)
Lymphoblastoid cell lines (LCL) are a highly successful model for evaluating the genetic etiology of cancer drug response, but applications using this model have typically focused on single drugs. Combination therapy is quite common in modern chemotherapy treatment since drugs often work synergistically, and it is an important progression in the use of the LCL model to expand work for drug combinations. In the present work, we demonstrate that synergy occurs and can be quantified in LCLs across a range of clinically important drug combinations. LCLs have been commonly employed in association mapping in cancer pharmacogenomics, but it is so far untested as to whether synergistic effects have a genetic etiology. Here we use cell lines from extended pedigrees to demonstrate that there is a substantial heritable component to synergistic drug response. Additionally, we perform linkage mapping in these pedigrees to identify putative regions linked to this important phenotype. This demonstration supports the premise of expanding the use of LCL model to perform association mapping for combination therapies.